2018
DOI: 10.1371/journal.pone.0195008
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of Pantoea agglomerans-derived lipopolysaccharide prevents development of atherosclerosis in high-fat diet-fed apoE-deficient mice via ameliorating hyperlipidemia, pro-inflammatory mediators and oxidative responses

Abstract: Pantoea agglomerans (P. agglomerans) is a Gram-negative bacterium that grows symbiotically with various edible plants, and the oral or sublingual administration of lipopolysaccharide derived from P. agglomerans (LPSp) have been suggested to contribute to prevention of immune-related diseases. Our previous study indicated that orally administered LPSp was shown to exhibit an LDL-lowering effect in hyperlipidemic volunteers; however, a preventive effect of LPSp on atherosclerosis is unclear. The present study at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 50 publications
3
34
0
1
Order By: Relevance
“…A growing body of evidence indicates that SAMP8 mice exhibit AD-like pathology and cognitive decline that result from aging and oxidative stress without genetic factors that act proximally on AD etiology [ 30 ]. Considering that orally administered LPSp has a beneficial effect on glucose/lipid metabolism [ 16 ], the present study used SAMP8 mice as a mouse model of AD to evaluate LPSp effects on HFD-induced AD progression. Consistent with recent studies using an HFD-fed SAMP8 [ 21 , 31 ], the present data demonstrated that chronic HFD feeding induces a significant increase in BW, caloric intake, fasting insulin level, HbA1c, and the glucose AUC in the OGTT, which is associated with an impairment of memory performance in the MWM test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A growing body of evidence indicates that SAMP8 mice exhibit AD-like pathology and cognitive decline that result from aging and oxidative stress without genetic factors that act proximally on AD etiology [ 30 ]. Considering that orally administered LPSp has a beneficial effect on glucose/lipid metabolism [ 16 ], the present study used SAMP8 mice as a mouse model of AD to evaluate LPSp effects on HFD-induced AD progression. Consistent with recent studies using an HFD-fed SAMP8 [ 21 , 31 ], the present data demonstrated that chronic HFD feeding induces a significant increase in BW, caloric intake, fasting insulin level, HbA1c, and the glucose AUC in the OGTT, which is associated with an impairment of memory performance in the MWM test.…”
Section: Discussionmentioning
confidence: 99%
“…The drinking water was changed weekly, and the concentration of LPSp was adjusted according to the average BW and amount of water consumption. The dose of LPSp was determined to be the sufficient dose required to achieve preventive effects as estimated from previous studies (0.1–1 mg/kg BW/day) [ 8 , 10 , 16 ]. BW, food intake, and water intake were recorded weekly.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…P. agglomerans derived LPS has anti-cancer properties in B16 melanoma model in mice [20], and an oral administration of this molecule contributed to prevention of atherosclerosis and hypertension [21].…”
Section: Introductionmentioning
confidence: 99%